Water quality index of Sungai Pahang - Hafidz Arif, Osman (2013)
Sungai Pahang is a river in Malaysia that is located at Pahang which is significantly degrading due to human activities as well as urbanization in the area. A study is conducted at selected area of the river to determine the water quality in Sungai Pahang at Kuala Pahang due to the development of Pekan during dry and wet time based on water quality parameters Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Dissolved Oxygen (DO), pH, Suspended Solids (SS) and Anmioniacal Nitrogen (NH 3 -N) in order to classify the river based on Water Quality Index (WQI) from the Department of Environment (DOE). DO and pH were analyzed as in-situ measurement while the rest of the parameters were analyzed in the laboratory. The selected stations was at near the restaurant area (Station 1), near to the recreational park (Station 2) and near to the construction site (Station 3). It was found that during dry time, the quality of water degrades significantly compared to during wet time for almost each water quality parameter. During dry time, Sungai Pahang can be classified as Class 2 while during wet time is classified under Class 3. Based on the outcomes, the water quality of Sungai Pahang is slightly polluted based on the calculation of WQI.